MUGBAS: a species free gene-based programme suite for post-GWAS analysis. (11th March 2015) - Capomaccio, S.; Milanesi, M.; Bomba, L.; Vajana, E.; Ajmone-Marsan, P.
Abstract : Genome Wide Association Studies between molecular markers and phenotypes are now routinely run in model and non-model species. However, tools to estimate the probability of association of functional units (e.g. genes) containing multiple markers are not developed for species other than humans. Here we introduce MUGBAS (MUlti species Gene-Based Association Suite), software that estimates the P -value of a gene using information on annotation, single marker GWA results and genotype. The software is species and annotation independent, fast, highly parallelized and ready for high-density marker studies. Availability and implementation : https://bitbucket.org/capemaster/mugbas Contact: capemaster@gmail.com